Monitoring Crimean-Congo haemorrhagic fever virus RNA shedding in body secretions and serological status in hospitalised patients, Turkey, 2015 - (:unkn) unknown (EUR CENTRE DIS PREVENTION & CONTROL, 2020)
Introduction: Crimean-Congo haemorrhagic fever (CCHF) is a tick-borne disease in Africa, Asia, the Balkan peninsula, the south-east of Europe and the Middle East, with mortality rates of 3-30%. Transmission can also occur through contact with infected animals or humans. Aim: This observational, prospective case series aimed to investigate detectable viral genomic RNA in whole-body fluids and antibody dynamics in consecutive daily samples of patients diagnosed with CCHF until discharge from hospital. Methods: We tested 18 patients and 824 swabs and sera with RT-PCR and 125 serum samples serologically. Results: The longest duration until clearance of viral RNA was 18 days from serum collection and 18, 15, 13, 19 and 17 days, respectively, from nasal, oral, genital (urethral or vaginal) and faecal swab, and urine. In seven patients, viral load decreased in serum at the same time as it increased in urine or persisted at the same logarithmic values. Despite clearance in serum, viral RNA was detected in faeces and genital swabs in two and three patients, respectively. Viral clearance from body fluids occurred earlier than from serum in eight patients on ribavirin treatment. The shortest seroconversion time was 3 days after symptom onset for IgM and IgG. Seroconversion of IgG occurred until Day 14 of symptoms. Conclusion: We report persistence of viral RNA in urine, faeces and genital swabs despite serum clearance. This may indicate a need for extending isolation precautions, re-evaluating discharge criteria and transmission risk after discharge, and considering oral swabs as a less invasive diagnostic alternative.
Keywords: SEXUAL TRANSMISSION; URINE; SAMPLES